Temperature- and water-induced structural transformations in Ba(Ce0.7Zr0.1Y0.1Yb0.1)O3-δ proton conducting electrolyte - Ivan Ivanov; Dmitry Tsvetkov; Vladimir Sereda; Dmitry Malyshkin; Anna Sereda; Petr Zakiryanov; Roman Yagovitin; Andrey Zuev (Chimica Techno Acta)
The crystal structure of Ba(Ce0.7Zr0.1Y0.1Yb0.1)O3–δ was studied depending on temperature in dry and wet atmosphere using in situ high temperature X-ray powder diffraction. Phase transition from tetragonal I4/mcm to cubic Pm-3m structure was shown to occur in Ba(Ce0.7Zr0.1Y0.1Yb0.1)O3–δ upon heating from 25 up to 1000 °C irrespective of air humidity. The cubic Pm m and tetragonal I4/mcm phases possess comparable coefficients of linear thermal expansion (CTEs), 10.6·10–6 K–1. Even in very dry atmosphere (10–4 atm H2O), chemical expansion caused by hydration contributes significantly to the observed structural transformations and the variation of the unit cell parameters of Ba(Ce0.7Zr0.1Y0.1Yb0.1)O3–δ.